Features of using SLA‑technology in the manufacture of molds for lost wax casting - K. V. Nikitin; V. N. Dyachkov; S. V. Kharchenko; D. M. Yudin; K. A. Yudina (Литьë и металлургия)
The results of using SLA‑technology in the manufacture of molds for obtaining wax models in lost wax casting are presented. 3D printing modes of molds have been developed to ensure the required roughness of the working surfaces and durability of the resulting molds. The optimal parameters for pressing the wax composition into molds made using SLA technology have been established. It is shown that the use of SLA technology for the manufacture of molds makes it possible to obtain wax models and castings of the required quality. An experimental technology has been developed for the production of castings from bronze by casting according to smelted models.